Molecular biology of the arterial wall - Schettler, Gotthard (Veröffentlichungen aus der Geomedizinischen Forschungsstelle der Heidelberger Akademie der Wissenschaften, Supplement zu den Sitzungsberichten der Mathematisch-naturwissenschaftlichen Klasse Jahrgang 1987, 1987)
The outstanding contributions to this volume are designed to shed light on some fields of cell biology and cellular pathology, including newly observed phenomena of cell-cell interactions, which might be applicable in studying the pathological process of atherosclerosis. The topics included cover: lipoproteins and lipoprotein receptors; growth factors; endocytosis and exocytosis; ONC Genes and proliferative disease; white blood cells; prostaglandins and leukotrienes; and the biology of smooth muscle and endothelium. The volume provides a complete summary of the most important developments in the field with great impact for arteriosclerosis research